Effects of resistance exercises on glycemic control, muscle strength, and body composition in patients with Type 1 diabetes Mellitus: Systematic review: Effects of resistance exercise in Type 1 Diabetes - F. Camilo, Victor; R. Costa, Matheus A.; L. Xavier , Larissa R.; U. Vitória , Estela; M. F. Sudré , Tamyris; Oliveira, Rodrigo Franco de (Manual Therapy, Posturology & Rehabilitation Journal, 2025)
Background: Type 1 diabetes Mellitus (T1DM) is a chronic condition characterized by an absolute deficiency of insulin, requiring rigorous glycemic control to prevent acute and chronic complications. Evidence suggests that physical exercise can positively influence glycemic control, although its acute effects on blood pressure (BP) and glycemia in adults with T1DM are still poorly understood. Objective: To evaluate the effects of resistance training on glycemic control, muscle strength, and the incidence of hypoglycemic episodes in patients with T1DM. Methodology: This study will be conducted thru a systematic review of clinical trials and observational studies published between the years 2014 and 2024. Studies addressing the effects of resistance training in patients with T1DM will be included, focusing on parameters such as glycemic control, muscle strength, and comparisons with other types of exercise or sedentary groups. Data collection will be conducted by independent reviewers, who will extract and record relevant information about the resistance training protocols used, clinical outcomes, and possible adverse events, such as episodes of hypoglycemia. Conclusion: It is expected that the systematic review will provide consistent evidence on the benefits of resistance training as a complementary strategy in the management of T1DM. By better understanding its effects on glycemic control and muscle strength, as well as the associated risks, especially regarding hypoglycemia, it will be possible to more accurately guide the prescription of physical exercises for this population, contributing to an improvement in the quality of life and clinical prognosis of patients.